The Oxford companion to ships & the sea - Kemp, Peter, 1904-1992; Milne, Peter, 1924- (London : Oxford University Press, 1976)
This new Companion will help its readers to gather the flowers of the sea, presenting in its 3,700 articles information which can otherwise be gleaned only with the help of an extensive library. The Companion is international in scope and covers the seafaring history of the world from earliest times to the present. At its heart are the short biographies of those who have left their mark upon the sea -- the navigators and explorers, naval and merchant seamen, marine designers, writers and artists, pirates and inventors. Yachtsmen and their craft, and the phenomenal growth of their sport in recent years, are given due place. Included too are definitions of technical seamanship, accounts of naval battles, histories of famous ships, descriptions of types of vessels, and articles on the development and principles of shipbuilding, navigation, seamanship, diving, fishery, and the lore and customs of the sea. The main articles are written by specialists in their subjects; other contributors are generally well-known maritime authors who have long studied maritime history in all its aspects. - Jacket flap.
Includes much information on polar ships, explorers, etc.
Keywords: Naval art and science -- Dictionaries; Dictionary